Antara Pembaca Anak atau Dewasa: Membuka Tabir Fiksi Semua Ikan di Langit: Between Children and Adult Readers: Uncovering Fiction Semua Ikan di Langit - Muhammad Fadli Muslimin; Achmad Zaki (Kantor Bahasa Provinsi Maluku, 2022)
Issues regarding children's literature are often only contained and discussed as didactic works that question the moralistic and dignity of children's minds. The storytelling aspect of children's literature is not entirely about this. This study aims to provide an overview of the dimensions of children's literature not only about didactic elements but also contains a discourse on how children have storied and their orientation is not only for children but also for adult readers. In analyzing the work, this research uses a content analysis method with a critical discourse analysis approach that focuses not only on the structure but also on the context. The results of this study were: first, the use of anthropomorphism in the depiction of characters opens an exploration of the world of children from the point of view of modern fiction; second, there is an effort to place various social contexts in the child's world; third, the existence of escapism fantasies that easily digested by adult readers, but difficult for children; fourth, the interpretation of the child's world is in the authority of adult readers; fifth, the excavation of the critique leaves room for new questions to be investigated. Keywords: didactic, adult reader, children reader, escapism